TRAINING ON BUMDES ACCOUNTING BASED ON MANAGER IO SOFTWARE AT BUMDES BINA LAKSANA, GARUT - Yuliafitri, Indri; Mulyani, Sri; Armania, Gia Prima (LPPM Univ. Ibn Khaldun Bogor, 2024)
Improving the capacity of Village-Owned Enterprises (BUMDes) in financial management is an urgent need, given their role as the locomotive of the village economy. One of the main challenges faced by BUMDes is the low competency in transparent and accountable financial recording and reporting. To address this, Manager.io application-based accounting training was conducted at BUMDes Bina Laksana, Sukalaksana Village. The training included an introduction to basic accounting concepts and the use of the Manager.io application, including transaction recording features and automatic financial report generation. The results showed an improved understanding of accounting by BUMDes managers and their ability to use digital technology to improve efficiency and accountability. In addition, post-training mentoring ensures the sustainability of the application implementation. This step is expected to support more professional and competitive BUMDes financial management in the digital era.